2021
DOI: 10.3390/brainsci11060738
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Socially Assistive Robotics: Clinicians’ and Patients’ Perception of a Social Robot within Gait Rehabilitation Therapies

Abstract: A growing interest in Socially Assistive Robotics in Physical Rehabilitation is currently observed; some of the benefits highlight the capability of a social robot to support and assist rehabilitation procedures. This paper presents a perception study that aimed to evaluate clinicians’ and patients’ perception of a social robot that will be integrated as part of Lokomat therapy. A total of 88 participants were surveyed, employing an online questionnaire based on the Unified Theory of Acceptance and Use of Tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 37 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Notice that any failure of the robot during surgery could expose the patient to serious risk. Furthermore, this variable is connected to trust, since the increase in risk perception could be a result of trust absence [45][46][47][48].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Notice that any failure of the robot during surgery could expose the patient to serious risk. Furthermore, this variable is connected to trust, since the increase in risk perception could be a result of trust absence [45][46][47][48].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It is suggested that experimental research on the effectiveness of QR codes be carried out in the future. Reference [50] used the UTAUT questionnaire to propose the perception and acceptance of social robots in the physical rehabilitation scene. It is recommended to conduct a study on integrating social robots into multiple places for future work.…”
Section: Research Topics and Future Research Directionsmentioning
confidence: 99%
“…It is an equally promising, safe and well-tolerated method of therapy for patients with neurological disorders, including post-spinal-cord-injury (SCI) patients [30][31][32][33]. Modern multifaceted rehabilitation using RAGT not only has a beneficial effect on improving the sensorimotor, kinematic and autonomic functions, but it also allows for a greater sense of control over one's own body and independence, thereby contributing to an improvement in psychological functioning and the subjective assessment of one's quality of life [5,[34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%